A method for preparing a sorbent for removing heavy metals from wastewater - Yusof, Nor Azah; Razak, Muhammad Raznisyafiq; Johari, Ili Syazana (2013)
The present invention relates to a method for preparing a sorbent for removing heavy metals from wastewater. Generally, the material used is selected from biomass fiber especially kenaf and oil palm empty fruit bunch (OPEFB). The method is able to remove heavy metals detrimental to health such as mercury, cadmium, zinc, copper, and lead and with noble metals such as gold, platinum and silver from industrial wastewater exhausted from various industries.